2017
DOI: 10.1002/rmb2.12055
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific serum anti‐Müllerian hormone concentration in Japanese women and its usefulness as a predictor of the ovarian response

Abstract: PurposeTo compare the ovarian response predictive ability of anti‐Müllerian hormone (AMH), follicle‐stimulating hormone (FSH), and estradiol (E2) and to determine the age‐specific distribution of serum AMH concentrations of Japanese women.MethodsThis was a multicenter (four‐site), observational, analytic, cross‐sectional Japanese study consisting of two parts: Study 1 (the prediction of the ovarian response of 236 participants who were undergoing controlled ovarian stimulation [COS]) and Study 2 (the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(45 reference statements)
3
11
0
Order By: Relevance
“…These findings were similar to the results of a previously reported multicenter, observational study . In this study, we measured AMH by the Access assays in more than 3000 Japanese women and the results indicated that AMH could be an accurate marker of ovarian response to stimulation as observed in the previous Gen II pre‐mix assay.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were similar to the results of a previously reported multicenter, observational study . In this study, we measured AMH by the Access assays in more than 3000 Japanese women and the results indicated that AMH could be an accurate marker of ovarian response to stimulation as observed in the previous Gen II pre‐mix assay.…”
Section: Discussionsupporting
confidence: 91%
“…We examined the correlation between each clinical parameters and value of antioxidant capacity. As expected, correlation was found between age, value of AMH and the number of ova collected, and value of AMH and total ovum account decreased as patients ages ( P < 0.001) . Contrary to the previous report, clinical parameters such as age and AMH showed no significant correlation with oxidative and antioxidant markers (Fig.…”
Section: Resultssupporting
confidence: 56%
“…On comparison, we found that serum AMH levels were 4.19±1.4, 3.54±1.4, 2.71±1.1 and 1.8±0.8 ng/ml among subjects in 'A', 'B', 'C' and 'D' sets, respec vely (Figure-2). Our findings, therefore, were evident to the established fact that supports declining pa ern of serum 15 AMH concentra ons as age advances.…”
Section: Figures-3 and 4 Demonstrate Distribu On Of Fsh And Lhsupporting
confidence: 70%
“…So they were separated into four sets as 'A', 'B', 'C' and 'D' having 25-30, 31-35, 36-40 and 41-45 years-old subjects, respec vely. Serum concentra ons of AMH decline as an individual's age 15 advances. So, we evaluated these subjects to rule out the possible varia ons in serum concentra ons of AMH with respect to age.…”
Section: Figures-3 and 4 Demonstrate Distribu On Of Fsh And Lhmentioning
confidence: 99%